BERENJENOL ISOLATED FROM Oxandra cf xylopioides (ANNONACEAE) AS INSECTICIDE - ROJANO, Benjamin A.; GAVIRIA M., Carlos A.; SÁEZ V., Jairo A.; YEPES, Francisco; MUÑOZ, Felipe; OSSA, Felipe (Vitae, 2009)
Berenjenol (21:24-epoxy-24-methyl-cycloartane) extracted from the leaves of Oxandra cf. Xylopioides, is evaluated as a biocide on Spodoptera frugiperda. Berenjenol is used at 25, 50, 100, 200 and 400 ppm, and is applied in an artificial diet of larvae in the second instar. The mortality percentage is determined at 24, 48 and 72 hours and LD50 and DL90 are calculated; the mortality analysis shows that berenjenol has a toxic effect, being the most mortal dose at 400 ppm. The effect of berenjenol is fast and effective, finding DL50 at 319.6 ppm after 24 h and similar values at 48 and 72 hours.